Best Fitting of NMO Equations and Depth Conversion - Ayman N Qadrouh*, Jose’M Carcione, Ahmed Salim, Zuhar Harith, . (2015)
The hyperbolic NMO equation is only exact for one interface in homogeneous and isotropic media. In heterogeneous media with many interfaces, this equation is an approximation and does not perform well at large offsets. To solve this problem, we consider several non- hyperbolic NMO equations, based on the average, RMS and root-mean-quartic (RMQ) velocities.